2023
DOI: 10.1037/pspi0000394
|View full text |Cite
|
Sign up to set email alerts
|

The business case for diversity backfires: Detrimental effects of organizations’ instrumental diversity rhetoric for underrepresented group members’ sense of belonging.

Abstract: Many organizations offer justifications for why diversity matters, that is, organizational diversity cases. We investigated their content, prevalence, and consequences for underrepresented groups. We identified the business case, an instrumental rhetoric claiming that diversity is valuable for organizational performance, and the fairness case, a noninstrumental rhetoric justifying diversity as the right thing to do. Using an algorithmic classification, Study 1 (N = 410) found that the business case is far more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 175 publications
1
33
0
Order By: Relevance
“…Otherwise, institutions might signal, albeit unintentionally, that they seek to check off as many “diversity boxes” as they can, particularly if they are lacking in one or more forms of diversity. Consistent with this possibility, both people of color and women in STEM feel less included in and are less attracted to organizations that only make an instrumental case for diversity (i.e., the usefulness of diversity in promoting the organization's success) as opposed to a moral case for diversity (i.e., the role of diversity in promoting fairness and equality; Georgeac & Rattan, 2022). In fact, moral (relative to instrumental) motives for diversity heighten organizations’ perceived attractiveness to dominant group members as well (Jansen et al., 2021).…”
Section: Policy Recommendationsmentioning
confidence: 99%
“…Otherwise, institutions might signal, albeit unintentionally, that they seek to check off as many “diversity boxes” as they can, particularly if they are lacking in one or more forms of diversity. Consistent with this possibility, both people of color and women in STEM feel less included in and are less attracted to organizations that only make an instrumental case for diversity (i.e., the usefulness of diversity in promoting the organization's success) as opposed to a moral case for diversity (i.e., the role of diversity in promoting fairness and equality; Georgeac & Rattan, 2022). In fact, moral (relative to instrumental) motives for diversity heighten organizations’ perceived attractiveness to dominant group members as well (Jansen et al., 2021).…”
Section: Policy Recommendationsmentioning
confidence: 99%
“…For scientists wishing to elevate psychological science's rigor and stand amongst policymakers, organizational stakeholders, and colleagues in mathematical and physical sciences, decontextualized research proliferating ineffective approaches to diversity across society is antithetical to these goals. For example, colorblind or instrumental approaches to diversity (Apfelbaum, et al., 2008; Apfelbaum et al., 2012; Georgeac & Rattan, 2022) remain a significant part of our field's past and present connection with diversity management strategies in organizations. And yet, our field provides very little evidence of such approaches' utility in attenuating hierarchy and, in fact, such strategies may contribute to inequality reproduction (Georgeac & Rattan, 2022; Starck et al., 2021).…”
Section: Implications Of Racial Inequality In Social Psychological Sc...mentioning
confidence: 99%
“…For example, colorblind or instrumental approaches to diversity (Apfelbaum, et al., 2008; Apfelbaum et al., 2012; Georgeac & Rattan, 2022) remain a significant part of our field's past and present connection with diversity management strategies in organizations. And yet, our field provides very little evidence of such approaches' utility in attenuating hierarchy and, in fact, such strategies may contribute to inequality reproduction (Georgeac & Rattan, 2022; Starck et al., 2021).…”
Section: Implications Of Racial Inequality In Social Psychological Sc...mentioning
confidence: 99%
“…frontiersin.org and the potential harm to Black, Latinx/e, Indigenous, women, and people from marginalized communities [11,12]. Specifically, the argument that diversifying the workforce will lead to better science and outcomes can inadvertently place heightened and unrealistic expectations on the few marginalized scholars brought onto a team and create an unwelcoming work environment for them where they will experience self-doubt and identity threat [13].…”
Section: Frontiers In Physicsmentioning
confidence: 99%
“…Concluded that moral arguments for diversity can lead to higher attractiveness of an institution for prospective employers. [12] found that for multiple marginalized groups (including women in STEM and African Americans in higher education) the business case for diversity undermined a sense of belonging to an organization and increased social identity threat, concluding that the business case deters rather than attracts diverse talent. [12] state that "the most prevalent organizational diversity case works against organizations' stated diversity goals, by paradoxically warding off the very groups they need to attract to become more diverse.…”
Section: Frontiers In Physicsmentioning
confidence: 99%